2022
DOI: 10.3390/cancers14184401
|View full text |Cite
|
Sign up to set email alerts
|

From HDAC to Voltage-Gated Ion Channels: What’s Next? The Long Road of Antiepileptic Drugs Repositioning in Cancer

Abstract: Cancer is a major health burden worldwide. Although the plethora of molecular targets identified in the last decades and the deriving developed treatments, which significantly improved patients’ outcome, the occurrence of resistance to therapies remains the major cause of relapse and mortality. Thus, efforts in identifying new markers to be exploited as molecular targets in cancer therapy are needed. This review will first give a glance on the diagnostic and therapeutic significance of histone deacetylase (HDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 226 publications
0
5
0
Order By: Relevance
“…Due to the lack of sufficient data, severe adverse reactions like delirium could not be assessed. Additionally, the gabapentin class of drugs, especially at higher doses, may affect the metastatic progression of tumor cells through disruption of Ca2 + signaling in Mat-LyLu cells in prostate cancer [ 52 , 53 ]. Even if the available data are largely controversial and inadequate at present, the use of pregabalin warrants caution [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of sufficient data, severe adverse reactions like delirium could not be assessed. Additionally, the gabapentin class of drugs, especially at higher doses, may affect the metastatic progression of tumor cells through disruption of Ca2 + signaling in Mat-LyLu cells in prostate cancer [ 52 , 53 ]. Even if the available data are largely controversial and inadequate at present, the use of pregabalin warrants caution [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the gabapentin class of drugs, especially at higher doses, may affect the metastatic progression of tumor cells through disruption of Ca2 + signaling in Mat-LyLu cells in prostate cancer [ 52 , 53 ]. Even if the available data are largely controversial and inadequate at present, the use of pregabalin warrants caution [ 53 ]. Consequently, the findings impaired the plausibility of using preemptive pregabalin in cancer-related surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive calcium influx into neurons can trigger various neurotoxic processes, including excitotoxicity and apoptosis, leading to neuronal injury and cell death. VPA mitigates these neurotoxic effects by reducing calcium influx through L-type channels, protecting neurons from damage and promoting neuronal survival [30] .…”
Section: Mechanism Of Action Of Valproic Acid Through Ionchannelmentioning
confidence: 99%
“…Recently, it was shown that VPA exerts an inhibitory effect on histone deacetylation. This, together with its ability to block the voltage-gated Na + and Ca ++ channels, both of which are considered tumor markers, has prompted the suggestion of its use in breast, prostate, and other types of cancers [113].…”
Section: Valproic Acid (Vpa)mentioning
confidence: 99%